Calcium and phosphorus serum levels in macaws (Ara sp) kept in captivity in Lima, Peru - Carlos Erazo, Nancy (2016)
The aim of the study was to determine the values of serum calcium and phosphorus in macaws (Ara sp) kept in captivity in three zoos in the department of Lima, Perú. All available births were sampled. There were 34 adult birds in 4 species (9 Ara macao, 14 Ara ararauna, 4 Ara chlropterus and 7 Ara severus). Blood samples (0.8 ml) were taken from the jugular vein in vacuum tubes without anticoagulant. Serum calcium and phosphorus values were determined by a colorimetric method. The mean values of calcium was 9.70 ± 1.48 mg/dl and phosphorus was 6.08 ± 1.42 mg/dl. By species, calcium values were: A. ararauna 9.67 ± 1.68 mg/dl, A. chloropterus 9.47 ± 1.80 mg/dl, A. macao 9.90 ± 1.75 mg/dl, A. severus 9.60 ± 0.35 mg/dl, and for phosphorus were: A. ararauna 6.03 ± 1.45 mg/dl, A. chloropterus 7.05 ± 2.12 mg/dl, A. macao 6.14 ± 1.35 mg/ dl, A. severus 5.54 ± 0.87 mg/dl. Significant differences in the levels of calcium and phosphorus were observed among the origin of birds.